Multiwavelength Brillouin-erbium Fiber Laser in Linear Cavity - Azhan M.N.M.; Cholan N.A.; Talib R.; Sulaiman A.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Brillouin scattering; Erbium; Fiber lasers; Fibers; Mirrors; Photonics; Pumping (laser); Brillouin erbium fiber lasers (BEFL); Brillouin-erbium fiber lasers; Fiber nonlinearities; Low thresholds; Multiwavelength; Stimulated Brillouin; Virtual mirror; Wide tunability; Single mode fibers